The aorta can act as a site of naıve CD41 T-cell priming - Macritchie, N; Grassia, G; Noonan, J; Cole, J; Hughes, C; Schroeder, J; Benson, R; Cochain, C; Zernecke, A; Guzik, T; Monaco, C; Garside, P; et al. (Oxford University Press, 2019)
Aims - Aortic adaptive immunity plays a crucial role in atherosclerosis; however, the precise mechanisms leading to T cell activation in the arterial wall remain poorly understood. Methods and Results - Here we have identified naïve T cells in the aorta of wild-type and TCR transgenic mice and we demonstrate that naïve T cells can be primed directly in the vessel wall with a similar activation profile to splenic and lymphoid T cells. Aortic homing of naïve T cells is regulated at least in part by the P-selectin glycosylated ligand-1 (PSGL-1) receptor. In experimental atherosclerosis the aorta supports CD4+ T cell activation selectively driving Th1 polarization. By contrast, secondary lymphoid organs display Treg expansion. Conclusions - Our results demonstrate that the aorta can support T cell priming and that naïve T cells traffic between the circulation and vessel wall. These data underpin the paradigm that local priming of T cells specific for plaque antigens contributes to atherosclerosis progression.